2017
DOI: 10.20950/1678-2305.2017v43n2p207
|View full text |Cite
|
Sign up to set email alerts
|

A diní­¢mica sazonal das pescarias de pequena escala na Amazônia é definida pelo pulso hidrológico

Abstract: O presente estudo analisou a dinâmica de uma pescaria de pequena escala na Amazônia, em associação com o ciclo hidrológico. Dados de desembarque pesqueiro foram coletados, diariamente, no período de fevereiro/2007 a janeiro/2008, no Porto Panairzinha em Manacapuru, Amazonas-Brasil (3º 18'33"S e 60º 33'21"W). Os resultados mostraram que a frota atuante no Lago grande é composta por canoas motorizadas e barcos de pesca. Sendo o primeiro superior ao segundo em número. A média do pescado desembarcado foi de 274,15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
16
1
1
Order By: Relevance
“…Fisheries in the Madeira River region are classified as small-scale artisanal fishing and present traits common to fishing activities conducted in other areas of the Amazon basin, such as being multi-species, multi-equipment and seasonal (Doria et al, 2012). Hydrological seasonality interferes with the total production and catch composition of fish species, since fish stocks are synchronized with river water level variations due to their migratory reproduction and dispersal processes (Garcez et al, 2017;Lima et al, 2017). Meanwhile, fishers demonstrate knowledge of the fishing environment and adapt to these variations to succeed in their livelihood (Isaac et al, 2015;Garcez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fisheries in the Madeira River region are classified as small-scale artisanal fishing and present traits common to fishing activities conducted in other areas of the Amazon basin, such as being multi-species, multi-equipment and seasonal (Doria et al, 2012). Hydrological seasonality interferes with the total production and catch composition of fish species, since fish stocks are synchronized with river water level variations due to their migratory reproduction and dispersal processes (Garcez et al, 2017;Lima et al, 2017). Meanwhile, fishers demonstrate knowledge of the fishing environment and adapt to these variations to succeed in their livelihood (Isaac et al, 2015;Garcez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrological seasonality interferes with the total production and catch composition of fish species, since fish stocks are synchronized with river water level variations due to their migratory reproduction and dispersal processes (Garcez et al, 2017;Lima et al, 2017). Meanwhile, fishers demonstrate knowledge of the fishing environment and adapt to these variations to succeed in their livelihood (Isaac et al, 2015;Garcez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fishing effort (f): this is the index that is related to fishing mortality (FAO, 1988), as well as the number of fishers multiplied by the days of actual fishing (Petrere Junior, 1978). It was inserted into the model by the graphical function, defined by the variables, Negro River level by the monthly value of (f), and indicated that the two variables are of a direct nature, meaning that their values increase or decrease proportionally with one another (Cardoso and Freitas, 2008;Hurd et al, 2016;Garcez et al, 2017).…”
Section: Replacement Ratementioning
confidence: 99%